2019
DOI: 10.1021/acs.jpcc.9b01063
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone as Potential Nonlinear Optical Material: A Combined Theoretical, Structural, and Spectroscopic Study

Abstract: In this work, we propose the synthesis of a novel bromine chalcone (E)-3-(2-bromophenyl)-1-(2-((phenylsulfonyl)­amine))­phenyl)­prop-2-en-1-one (BRC) that has been crystallized by the slow evaporation technique. The second-order molecular optical scattering and two-photon absorption­(2PA) spectrum of the BRC molecule dissolved in dimethyl sulfoxide (DMSO) were evaluated by using hyper-Rayleigh scattering and the femtosecond tunable Z-scan techniques. The first-order hyperpolarizability of BRC dissolved in DMSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 62 publications
1
27
0
1
Order By: Relevance
“…Here the large 6-311+G(d) Pople split-valence basis set is used combined with the CAM-B3LYP. In favor of usingthe PCM model, recent theoretical studies of NLO properties of molecules immersed in solvent media have shown a good agreement with the experimental data for the Hyper-Rayleigh Scattering first hyperpolarizability [5,13,21,25].…”
Section: Solvent Mediamentioning
confidence: 70%
See 1 more Smart Citation
“…Here the large 6-311+G(d) Pople split-valence basis set is used combined with the CAM-B3LYP. In favor of usingthe PCM model, recent theoretical studies of NLO properties of molecules immersed in solvent media have shown a good agreement with the experimental data for the Hyper-Rayleigh Scattering first hyperpolarizability [5,13,21,25].…”
Section: Solvent Mediamentioning
confidence: 70%
“…The study of organic materials exhibiting nonlinear optical properties has been of great interest in the recent years, partly due to the ease handlingof these compounds as compared with inorganic materials.Organic materials with large third-order nonlinear optical (NLO) properties are promising for several applications in photonic technologies [1,6,7,14,17,30,31]. Triazole and its derivatives, as the 1, 2, 3-triazole, have a simple structure exhibiting interesting nonlinear optical properties [1,5,28] and in addition present a number of functionalities in the fight against pathologies, such as antimycotic [12], antiviral [15], anticonvulsant [8], antidepressant [26], anti-inflammatory [16], antifungal [9] and analgesic [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the dynamic case an increase in the electric parameters as a function of the dielectric constant presents oscillations. In DMSO, which is a common solvent medium used in the HRS experiment, the varies from 44 × 10 −30 (static case) to 86 × 10 −30 (dynamic case); these values are great as compared with the values for other organic compounds [21].…”
Section: Study Of the Hyper-rayleigh Scattering First Hyperpolarizabimentioning
confidence: 99%
“…For these reasons, there is a pressing need to find novel materials with efficient applicability in the field of optoelectronics and photonics. Although the biological uses of chalcones have been investigated widely in recent times, the use of chalcones as potential optoelectronic materials is still a topic of great research interest [4]. Often, in a bid to get around the reported poor luminescence properties of chalcone-based organic molecules, partly due to the quenching pro-cesses from the intramolecular torsional motions and cis-trans isomerization in the α, β-unsaturated ketone moiety, the complexation method is often a way out towards improving their optical properties [3] [13].…”
Section: Introductionmentioning
confidence: 99%